PEMBUATAN MINUMAN PROBIOTIK DAUN JAMBU BIJI (Psidium guajava L.) DENGAN BAKTERI ASAM LAKTAT - Oktaria, Taskiya Sindy; Nofitasari, Shindi; Susanti, Alifah Dwi; Muflihati, Iffah; Suhendriani, Sari; Umiyati, Rini; Ujianti, Rizky Muliani Dwi; Nurdyansyah, Fafa; Affandi, Arief Rakhman (Biosel Biology Science and Education, 2025)
Probiotic drinks contain a number of live bacteria that are beneficial for maintaining the natural microflora of the human digestive tract in a balanced state. Guava plants are plants that have the potential to be used as functional foods, one of which is probiotic drinks. The purpose of this study was to determine the characteristics of probiotic drinks with treatments, namely different types of guava leaves and different cultures of lactic acid bacteria used. The experimental design used is a completely randomized design (CRD) with 2 treatments, namely differences in the type of guava leaves and LAB used. The pH analysis results showed that white guava with Lactobacillus acidophillus culture had the most acidic pH. The test results of red guava with Lactobacillus casei culture get the lowest value of total soluble solids and the brightest color. The highest viscosity is white guava with Lactobacillus casei culture. Descriptive tests of all attributes were not significantly different except for the sour taste attribute. Hedonic test showed that panelists disliked probiotic drinks with Lactobacillus casei culture. Keywords: Probiotics Drink, Guava Leaf, Leaf Type, Lactobacillus casei, Lactobacillus acidophillus